Occupational Risks: A Follow-up Method Based on Individual Work History Records Including the Environmental Aspects of the Workplace - Martin, J. M.; Robaux, P. (Methods of Information in Medicine, 1989)
This article analyzes the Curriculum Laboris or career reconstruction as a means of studying the occupational risks of employees. A type of Curriculum Laboris which makes the established record easier to use has been suggested. The authors point out some advantages to be expected from the proposed computerized method. The usefulness of the proposed Curriculum Laboris is largely conditioned by lack of standards for guiding data collection by physicians. Finally, the Curriculum Laboris has been considered as an element of a larger information system.
Keywords: Occupational Risk; Follow-up; Information System; Curriculum Laboris; Career Reconstruction